Disparities in earnings and education in India - P. Geetha Rani (Cogent Economics & Finance, 2014)
This paper studies the impact of different levels of education, religion, caste as well as the impact of living in urban and rural communities on earnings in India. Besides these conventional stratification, yet another academic caste which influence earnings-the English language ability, is also examined. The paper uses a large cross-section sample of India Human Development Survey to estimate Mincer and augmented Mincer equations. The rates of return estimates obtained in these data and method confirm that returns to education increase with the level of education across location, caste-religion and English language ability. Returns to lower levels of education are low across different groups, indicating the low quality of basic schooling in the country. Returns to higher education vary at a great deal ranging between 4.9% among the rural workers and 38.2% among fluent English ability group. This is in contrast to Duraisamy reporting the highest returns to secondary education in India, between the period 1983 and 1993 - 1994. In a decade's time, with changes in the economy and in the labour market, higher education especially the English language ability along with higher education brings in the highest wage premium.
Keywords: 330; returns to education; earnings; disparities